A snapshot of characteristics and dynamics of Austrian exporting firms - Robert Stehrer; Bernhard Dachs (FIW - Research Centre International Economics, 2022)
In view of the importance of the export economy for Austria this study examines the role and characteristics of Austrian exporting firms compared with non-exporting firms. Specifically, it assesses how the share of exporting firms has developed in recent years, whether exports have become more important for firms over time and to what extent exporters have an advantage over other firms (export premium). The results show that about two third of the Austrian manufacturing firms are engaged in exporting activities and indicate that - in line with existing literature - exporting firms are larger, more productive, generate higher surpluses, invest more, and spend more on environmental protection than non-exporters. Further, the results highlight that only a small number of firms account for a large share of Austrian manufacturing exports. Finally, the results point towards a mutual positive relationship between export behaviour, productivity, and R&D expenditures.
Keywords: D22; F14; 330; export premium; firm-level analysis; productivity and exporting